The Impact of Outdoor Sports on Preschool Children’s Motor Skills Development - Usman Saadu (Indonesian Journal of Sport Management, 2022)
The main purpose of this study was to examine the impact of outdoors sports on preschool children’s motor skills development in Ilorin Metropolis. The study adopted a pretest-posttest control group quasi-experimental research design. The population of this study consisted of all preschool children in public schools the Ilorin Metropolis, Kwara State. Purposive sampling technique was used to select 10 public schools who had preschooler with motor skill coordination problem. The sample size for this study comprised of 47 preschoolers who had motor skills coordination problems. The instrument was titled “Preschoolers performance scores (PPS)” were used to elicit information. It consisted of 10 items on a 3 likert-scale; options on “low”, “moderate” and “high” based on what preschoolers were able to do before and after exposing them to outdoor sports. Some of the items were kicking a ball at 5m target, throwing at a 2m target, running forward, balancing on right and left foot, throwing and catching a ball. The keys used were low 0.00-0.09, moderate 1.0-1.4 and high 1.5-2.5. Instruments were validated by lecturers in the department of Human Kinetics and reliability score was 0.79. The data were analyzed using frequency counts and percentage and Analysis of Covariance (ANCOVA) at 0.05 level of significance. The findings of the study revealed that there was a significant main effect of treatment on preschool children motor skill development (F(1; 47) = 264.448, P < 0.05).  also, there was no significant main effect of gender on preschool children motor skill development (F (1; 47) =1.422; P > 0.05) and there was no significant interaction effect of treatment and gender on preschool children motor skill development ( (F (1; 47) =1.538; P >0.05). The study concludes that sports especially outdoor activities have positive impact on preschoolers’ motor skills development. Based on the findings, the study recommends among others that; teachers in preschools should be encouraged on the use of outdoor sports in improving motor skills development in children and workshops and trainings should be organized by school owners regularly, in order to educate teachers on new ways of improving motor skills development.